Intestinal Parasites and Sanitary Practices among the Rural Children - Azam, SA Sultana; Bhuiyan, MM Rahman; Chowdhury, M Zaforullah; Miah, K Ali (TAJ: Journal of Teachers Association, 2009)
Infestation with intestinal parasites is a common problem throughout the world. It is estimated that at least one quarter of the world's population is clinically infected with intestinal parasites. In this article, we have tried to explore the relation between intestinal parasites and sanitary practices among the rural children in Bangladesh. doi: 10.3329/taj.v20i1.3081 TAJ 2007; 20(1): 01-05